Intercultural Theology KH. Hashim Asy'ari: Memadukan Kebudayaan, Keislaman, dan Nasionalisme di Indonesia - Achmad Muhibin Zuhri (Universitas Islam Tribakti Lirboyo Kediri, 2020)
Religion has two inherent characteristics. It will be transcendent if it is expressed as servitude to God. However, it becomes profane when articulated into fellow human beings' lives. Thus, religion cannot be separated from the influence of the culture in which humans exist. Through an intercultural theological approach, this study intends to show the thoughts of Kiai Hashim Asyari, who can integrate Sunni theological discourses relevant to Indonesian society's culture without reducing the fundamental values of faith. This study argues that Kiai Hashim's view of theological discourse can be introduced as the idea of